Observation on the therapeutic effect of probiotics on early oral feeding in the treatment of severe acute pancreatitis - Zhao, Yanan; Zhang, Rui; Wang, Shuling; Yang, Chunchun; Wang, Yang; Fan, Hongyun; Yang, Mingyue (Frontiers in Medicine, 2024)
Objectives To evaluate the clinical efficacy of probiotics and early oral feeding in patients with severe acute pancreatitis. Methods A prospective, randomized, controlled trial was conducted involving 66 patients, who were randomly divided into a control group (n = 32) receiving standard enteral nutrition and an observation group (n = 34) receiving additional Bifidobacterium quadruplex live bacterial tablets. Serum inflammatory markers, including white blood cells (WBC), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and C-reactive protein (CRP), were measured on days 1, 3, and 7 post-admission. Abdominal pain scores, the computed tomography severity index (CTSI), and the Bedside Index for Severity in Acute Pancreatitis (BISAP) scores were also assessed. Additionally, defecation time and the total duration of hospitalization were compared between the two groups. Results Inflammatory markers declined in all groups by the third day post-admission, with the observation group exhibiting a significantly greater reduction compared to the control group (p < 0.05). Similarly, from the first day to the third day, both groups experienced a decrease in abdominal pain scores, CTSI, and BISAP scores, with the observation group showing a significantly more pronounced decrease in BISAP scores compared to the control group (p < 0.05). By the seventh day of admission, inflammatory markers continued to decline in all groups compared to the third day, except for TNF-α levels, and the observation group demonstrated a significantly greater decrease compared to the control group (p < 0.05). Abdominal pain scores, CTSI, and BISAP scores also decreased further in both groups compared to the third day, with the observation group again showing a significantly greater improvement than the control group (p < 0.05). Additionally, the observation group had a significantly shorter time to bowel movement resumption (38.23 ± 2.31 h vs. 43.43 ± 2.75 h, p = 0.013) and total hospital stay compared to the control group (10.97 ± 0.35 days vs. 13.40 ± 0.50 days, p < 0.001). Conclusion Early oral ingestion combined with probiotics can reduce the levels of inflammatory factors, improve abdominal pain symptoms, alleviate pancreatic edema and shorten defecation time and hospital stay in patients with severe acute pancreatitis.